Efectos del cálculo del impuesto a la renta de las personas naturales en relación de dependencia en el Consejo Nacional de Competencias – período 2021 – 2023 en base a la reforma tributaria - Vera Mendieta, Andrés Xavier (2024)
This degree work generated the criteria and calculation to define the relevance of the income tax payment of natural persons in a dependency relationship, among them, those who belong to the National Skills Council during the period 2021- 2023. During its development, we took into consideration: Resolution NACDGERCGC20-00000077 published in the S.R.O. 359 of 12/29/2020, the Organic Law for Economic Development and Fiscal Sustainability after the COVID 19 pandemic, published in the S.R.O. 587 of 11/20/2021 and the Organic Decree Law for the Strengthening of the Family Economy published in S.R.O 335 of 06/20/2023........